Boosting low-temperature activity and thermal stability in light alkane oxidation by balancing confined Ru species and the MFI zeolite microenvironment - Jingjing Wang; Lianghui Xia; Yanfei Jian; Qiyuan Liu; Yujie Liu; Yani Wu; He Xu; Yaruo Zhao; Jingyao Wang; Zeyu Jiang; Jinghang Huo; Yanke Yu; et al. (Chemical Engineering Journal, 2026)

Hydroxysafflor Yellow A Attenuates Sepsis-Induced Cardiac Dysfunction by Inhibiting Ferroptosis via Activation of Thioredoxin - Yanke Chen; Xu Cai; Wenbin Nan; Zhenyu Peng (Cardiovascular Toxicology, 2026)

Swimming of Multi-Fish Swarms Simulated Using a Virtual Cell-Immersed Boundary Framework - Yanke Shi; Xufang Liu; Kangkang Xu; Bo Yin (Journal of Marine Science and Engineering, 2026)
To explore the influence of inter-formation variables on swimming performance during fish schooling, this paper adopts the sharp interface immersed boundary method based on virtual cells to conduct numerical research on the swimming of three-fish and four-fish swarms with different formations and spacings. The study finds that both streamwise spacing and lateral spacing have significant impacts on the swimming performance of fish schools. In the three-fish formation, when the tandem arrangement has a streamwise spacing of 1.3 times the body length (L), the trailing fish achieve the highest swimming efficiency; when the parallel arrangement has a lateral spacing of 0.25L, the fish in the middle position exhibits the optimal swimming performance. In the four-fish formation model, fish in symmetric positions within the same swarm have similar hydrodynamic performance. For the diamond formation, under the configuration of streamwise spacing 1.2L and lateral spacing 0.5L, the propulsive efficiency of the trailing fish is markedly diminished; however, for the rectangular formation, all trailing fish obtain lower swimming efficiency, and a stable 2S-type vortex structure appears in the wake under the configuration of streamwise spacing 1.5L and lateral spacing 0.5L, which is conducive to thrust generation. The conclusions of this paper can provide certain hydrodynamic advantages and support the development of bionic underwater vehicles and robot technology.

Optimization of hollow ZIF-8/GO composite imprinted membrane synthesis by polyphenol etching technique and study of its selective separation performance for ribavirin - Yilin Wu; Yanke Xu; Faguang Ma; Jingjing Zhen; Yue Li; Fanlei Kong; Ming Yan (Desalination, 2025)

Corrigendum to “Main lipid sources affecting key aroma volatile compounds in Chinese native chicken” [Food Chemistry 474 (2025) 142990] - Yanji Chen; Yongli Wang; Yanke Wang; Na Luo; Richun Cai; Yang Yu; Xu Zhang; Jinmei Zhu; Guiping Zhao; Jie Wen; Huanxian Cui (Food Chemistry, 2025)

Construction of UiO-66-NH2-based imprinted nanocages on nanofiber membranes for selective separation of Nd (III) - Yanke Xu; Faguang Ma; Ming Yan; Yue Li; Yilin Wu (Chemical Engineering Journal, 2025)

Main lipid sources affecting key aroma volatile compounds in Chinese native chicken - Yanji Chen; Yongli Wang; Yanke Wang; Na Luo; Richun Cai; Yang Yu; Xu Zhang; Jinmei Zhu; Guiping Zhao; Jie Wen; Huanxian Cui (Food Chemistry, 2025)

Impact of the potassium transporter TaHAK18 on wheat growth and potassium uptake under stressful K+ conditions - Tengfei Liu; Yanan Zhang; Yumin Xie; Ruipeng Yang; Mengying Yuan; Yanke Li; Haixia Xu; Xinli Zhu; Tengzhao Song; Xiyong Cheng (Journal of Plant Physiology, 2025)

Flood Wave Superposition Analysis Using Quantitative Matching Patterns of Peak Magnitude and Timing in Response to Climate Change - Qiumei Ma; Lihua Xiong; Chong-Yu Xu; Rongrong Li; Changming Ji; Yanke Zhang (Water Resources Management, 2021)

Spatiotemporal patterns of satellite precipitation extremes in the Xijiang River Basin: From statistical characterization to stochastic behaviour modelling - Qiumei Ma; Changming Ji; Lihua Xiong; Yi Wang; Chong‐Yu Xu; Yanke Zhang (International Journal of Climatology, 2021)
Given the threats from rainstorm events that have been intensified due to climate change, the investigation of heavy/extreme precipitation is attracting increasing attention. The investigation of extreme precipitation, with its restricted tools and data, is quite different from that of nonextreme precipitation. Satellite precipitation estimates (SPEs) are promising precipitation measurements due to fine spatial resolution. However, the spatiotemporal patterns of SPE extremes remain unclear. Therefore, this study attempted to systematically analyse the spatiotemporal patterns of extreme SPEs provided by the Tropical Rainfall Measurement Mission (TRMM) research product from statistical characterization to stochastic behaviour modelling. The statistical characterization was depicted using comprehensive extreme precipitation indices (EPIs), while the stochastic behaviour was modelled using the generalized Pareto distribution (GPD) to fit the ‘peak over threshold’ samples and employing the max‐stable process to fit the ‘block maximum’ samples (Max: annual 1‐day maximum, RX1day: monthly 1‐day maximum, and RX5day: monthly 5‐day maximum) of the TRMM data. The TRMM extremes were analysed across the Xijiang River Basin, China. The results of the statistical characterization revealed that compared with gauge precipitation, most TRMM EPIs were discovered to have higher temporal dynamic levels. Moreover, the spatial median of the return level for each return period derived from temporal TRMM extreme modelling with the GPD was lower than that from gauge extremes. The spatial dependence of Max in TRMM was weaker than that of either RX1day or RX5day, primarily due to different precipitation‐generating processes existing between two extreme events at annual scale compared with monthly scale. Each of the Max, RX1day, and RX5day in TRMM exhibited stronger spatial dependence than that in gauge extreme precipitation, maybe related to the area‐average‐based representation of the SPEs. These findings can enhance our insight into the spatiotemporal patterns of extreme satellite precipitation, which is beneficial for operational flood risk management.

Relationship between RAGE gene polymorphisms and cardiovascular disease prognosis in the Chinese Han population - Jinxiong Gao; Liehua Deng; Ying Wang; Yanke Shi; Xiaohua Xiao; Xueou Zheng; Hao Ren; Dingli Xu (Molecular Genetics and Genomics, 2017)

Lentiviral Vector-Induced Overexpression of RGMa in the Hippocampus Suppresses Seizures and Mossy Fiber Sprouting - Ling Chen; Baobing Gao; Min Fang; Jie Li; Xiujuan Mi; Xin Xu; Wei Wang; Juan Gu; Bo Tang; Yanke Zhang; Zhihua Wang; Ao Zhan; et al. (Molecular Neurobiology, 2017)

Association of Microtubule Dynamics with Chronic Epilepsy - Xin Xu; Yida Hu; Yan Xiong; Zhonggui Li; Wei Wang; Chao Du; Yong Yang; Yanke Zhang; Fei Xiao; Xuefeng Wang (Molecular Neurobiology, 2016)

CD147 is increased in HCC cells under starvation and reduces cell death through upregulating p-mTOR in vitro - Xingchun Gou; Xu Tang; Derek Kai Kong; Xinying He; Xingchun Gao; Na Guo; Zhifang Hu; Zhaohua Zhao; Yanke Chen (Apoptosis, 2016)

Chlorobenzene Destruction over Mesostructured CuO and MnO x Co-Modified CeO2 Catalyst: Activity and Activation Route - Chi He; Gaoshan Men; Yanke Yu; Hua Pan; Bitao Xu (Water, Air, & Soil Pollution, 2015)

ENT1 Inhibition Attenuates Epileptic Seizure Severity Via Regulation of Glutamatergic Neurotransmission - Zucai Xu; Ping Xu; Yalan Chen; Jing Liu; Yanke Zhang; Yaodong Lv; Jing Luo; Min Fang; Jun Zhang; Jing Wang; Kewei Wang; Xuefeng Wang; et al. (NeuroMolecular Medicine, 2015)